Penerjemah Berbasis Arificial Intellegence Dalam Proses Penerjemahan - Samsudin Hi Adam; Silvani Umar Ali (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the midst of rapid technological changes, the way translators work is also transforming. In the digital era, the development of translation technology continues with the presence of automatic translation platforms based on Artificial Intelligence (AI). This technology is capable of producing translations in seconds, although it still requires human editing. In the field of translation, there are many artificial intelligences (AI) engines being developed, one of which is Google Translate. A few years ago, Google Translate might have been unreliable. However, currently, Google Translate, which originally used Machine Translation (MT), has switched to using Neural Machine Translation (NMT) so that it can translate one sentence with more natural and accurate results. With its current developments, AI translation has made communication between languages easier and more efficient. This becomes a bridge that makes it easier for people from different language backgrounds to understand each other. In addition, the practicality and speed of machine translation also provides easy access to information. Despite significant advances in AI in translation, challenges remain. Therefore, even though AI is getting better, the role of humans in verifying and improving translation results is still